Epigenetic contribution to successful polyploidizations: variation in global cytosine methylation along an extensive ploidy series in Dianthus broteri (Caryophyllaceae). Issue 3 (2nd August 2016) - Alonso, Conchita; Balao, Francisco; Bazaga, Pilar; Pérez, Ricardo
Summary: Polyploidization is a significant evolutionary force in plants which involves major genomic and genetic changes, frequently regulated by epigenetic factors. We explored whether natural polyploidization in Dianthus broteri complex resulted in substantial changes in global DNA cytosine methylation associated to ploidy. Global cytosine methylation was estimated by high‐performance liquid chromatography (HPLC) in 12 monocytotypic populations with different ploidies (2×, 4×, 6×, 12×) broadly distributed within D. broteri distribution range. The effects of ploidy level and local variation on methylation were assessed by generalized linear mixed models (GLMMs). Dianthus broteri exhibited a higher methylation percent (˜33%) than expected by its monoploid genome size and a large variation among study populations (range: 29.3–35.3%). Global methylation tended to increase with ploidy but did not significantly differ across levels due to increased variation within the highest‐order polyploidy categories. Methylation varied more among hexaploid and dodecaploid populations, despite such cytotypes showing more restricted geographic location and increased genetic relatedness than diploids and tetraploids. In this study, we demonstrate the usefulness of an HPLC method in providing precise and genome reference‐free global measure of DNA cytosine methylation, suitable to advance current knowledge of the roles of this epigenetic mechanism in polyploidization processes.